The Kusama Retrospective and the Future of The Tel Aviv Museum of Art - Katz, Maya Balakirsky (Images, 2022)
Following two years of heavy COVID restrictions, the Tel Aviv Museum of Art opened the “first-ever retrospective in Israel” of the Japanese artist Yayoi Kusama. Beyond the pioneering artist that is the subject of the retrospective and what it says about the Israeli public that is drawn to her work, the exhibition also invites analysis into the restaging of art exhibitions originating in another country, in this case a German museum, with all the implications that such a venture raises in Israel. In breaking down the curatorial modus operandi of restaging a borrowed exhibition designed by the Gropius Bau Museum in Berlin in Tel Aviv, this paper explores the museological craft of restaging exhibitions. In its original conception, the Gropius Bau focused on Kusama’s art “from a European and particularly from a German perspective,” highlighting Kusama’s “influence” on the European art scene during the time she spent in Germany in the late 1960s. The Tel Aviv Museum made significant changes to this scholarly conceptual core, perhaps sensitive to any claim that positioned Berlin as a cosmopolitan city after the Holocaust, by opting for an “affective” visitor experience. The site-specific textuality of this endeavor foregrounds the Tel Aviv Museum’s performance of itself in its twin roles in the nation’s history and its internationalization of the country’s cultural capital. I suggest that the Kusama exhibition reflects a new direction for the broader practices of art curatorship in the oldest art museum in the country.